Study on the transmission path and timing scheduling for WSNs with heterogeneous nodes. Issue 1 (21st January 2019) - Zhao, Huiyuan; Mao, Yuxing; Cheng, Tao
Abstract : Purpose: Application environments of wireless sensor networks (WSNs) include heterogeneous nodes with different packet sizes, transmission abilities and tolerable delay times. This study aims to design a reasonable network topology and transmission timing for these heterogeneous nodes to improve the quality of service (QoS) of networks. Design/methodology/approach: In this paper, the authors treat node urgency and data packets as the basis of network clustering and to extend the network lifetime. The flow, energy consumption and residual energy of a node are included in the cluster head election. We also propose a delay evaluation function. Findings: All the nodes in the network are guaranteed to transmit to the sink nodes efficiently by planning the transmission order in each cluster. Originality/value: The simulation results show that the proposed method can balance node urgency and data packets path planning, which not only extends the lifetime of the network but also decreases network delay and improves the overall efficiency.